SISTEM INFORMASI PENGOLAHAN TUGAS AKHIR BERBASIS WEB - Marsella, Minhwa Mella; Anwariningsih, Sri Huning; Charolina, Astri (Gaung Informatika, 2015)
Processing final exam project is an aspect that is very important to know the students who submitted the final exam project such as the title of the submission process, filing seminars, and filing pendadaran. The purpose of this information is made systems simplify data processing and presentation of the information through the website. System design methods used to design the system using an object-based system design, for making this information system using PHP and uses a MySQL database. Website produced from this research about information processing Sahid University student thesis Surakarta. This information system is tested using black box testing, and found no problems in normal use, with these results mean the end of the task processing website otherwise good.